An ecosystem approach to knowledge management: Case studies of two Australian SMEs - Tan, Amanda; Chang, Vanessa (ACIS, 2008)
This study is centred on the premise that knowledge is personalised information which can be enriched through the process of learning, then shared and applied to practical situations to attain value. To highlight the complex nature of knowledge management (KM) as a set of practices and aimed to enhance collaboration, the concept of a Collaborative Leaning Ecosystem (CLES) is presented as holistic approach toward improving practical learning environments. In view of the pressing need for better KM in small-to-medium (SME) enterprises, the CLES framework is used to examine the KM positions of two Australian SMEs. Viewing each case as an 'organisational ecosystem', the holistic assessment of each SME exposes certain KM inefficiencies unique to the firm, which are addressed through a set of actionable KM strategies for improving the relationships among the components interacting within each organisational ecosystem.